Cross-Cultural Adaptation Among Young Afghan Refugees Returning from Iran to Afghanistan - Moravej, Masuma (Université d'Ottawa / University of Ottawa, 2014)
This study investigated certain aspects of the cross-cultural adaptation process of Afghan returnees who have repatriated from Iran to Afghanistan. The study’s particular focus is the issue of cross-cultural adaptation in the current context of Afghanistan; that is, what challenges face Afghans returning from Iran to their country of origin following years of exile in Iran. Afghan immigration to Iran has a long history. Using Young Yun Kim’s cross-cultural adaptation theory as the leading theoretical framework, the researcher investigated the cultural adaptation of those who have lived in Iran for more than 10 years and have repatriated voluntarily to Afghanistan at least three years before the data for this thesis were gathered. Semi-structured interviews were conducted for collecting primary data from participants for the thesis. Twelve young returnees from Kabul City, aged 18 to 40, volunteered to take part in the interviews. Results revealed that language barriers, cultural knowledge and environmental challenges were some of the dominant difficulties that returnees experienced after their repatriation. Furthermore, the findings showed that the three main strategies used by the young returnees to adapt to their unfamiliar, new environment of Kabul City included social interaction, using mass media, and keeping an open mind on current issues. The findings of the interviews revealed the ongoing changing nature of identity formation of the returnees after their repatriation to Afghanistan and, also the majority of participants (9 out of 12) voiced a strong sense of belonging and attachment to Afghanistan.
Keywords: cross-cultural adaptation; integration; intercultural interaction; repatriation; Afghan refugee